User satisfaction on virtual reality taekwondo training material - Nur Ain, Mohd Jelani (2019)
This study focuses on the design and development of Virtual Taekwondo Training Environment (VT2E) prototype as a supplementary material for self-directed Taekwondo training. Even though there are varieties of supplementary Taekwondo training materials available, most of them have limitations in supporting self-directed training. The results of the preliminary study clearly indicated the importance of self-directed Taekwondo training among the trainees and they are facing problems while performing self-directed training at home since they do not have proper supplementary training materials to guide them. Thus, the research aims to propose the VT2E prototype as a supplementary material for self-directed Taekwondo training which incorporates Virtual Reality (VR) and Motion Capture (MoCap) technologies which is to study the trainees’ satisfaction in terms of Engaging, Presence, Usefulness and Ease of Use. The methodology of this study consists of three phases, namely; information gathering, prototype design and development and evaluation which is adapted from Vaishnavi and Kuechler (2008). In providing a useful and effective training material, the prototype incorporates the Constructivist Theory and Theory of Flow. Perception, Pearson Correlation and Regression analyses were used to determine the effects of Engaging, Presence, Usefulness and Ease of Use on trainees’ Satisfaction in using the VT2E prototype. The results provided empirical support for the positive and statistically significant relationships between usefulness and ease of use on trainees’ satisfaction. However, Engaging and Presence did not have positive and significant relationships with satisfaction. As for the conclusion, this study has looked into the possibility of introducing a new approach of training through the use of the two technologies. It is hopeful that this prototype can be a guide for self-directed Taekwondo training in enhancing the skills and performances and indirectly fullfil the trainees’ satisfaction.